Gamify Beyond Borders! Using Gamification as a Catalyst for Globalization in Health Professions Education - Rabia Aftab,; Mahapara Khan,; Aun Ali, (Journal of the Pakistan Medical Association, 2025)
By definition, Globalization is the procedure of international interaction and integration across exchanges of opinions, outputs, notions and different aspects of culture. The globalization system applies substantial influence on the conditions, political workflow, culture, economic development, healthcare and education system around the world. It has highlighted the demand for global citizens.1 Rapid technological breakthrough have caused significant paradigm shifts in nearly every field, to the point that maintaining a competitive edge in a globalized market today necessitates pursuing educational opportunities beyond the conventional ones that produce knowledgeable, skilled, and driven workers.2 Globalization is a main player of innovation in Health Profession Education (HPE). In today’s era, medical education is rapidly evolving. Since the digital learning platforms are rising, culturally adaptive educational, engagement, and the need for scalable strategies have also been increasing.3 Gamification grants a powerful tool to standardize competencies, overcome geographical barriers, and improve learning outcomes across diverse healthcare systems. It is the application of game design elements in non-gaming contexts.4 Continued...